2007
DOI: 10.1016/j.clim.2007.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing CD8+ T cell responses elicited by peptide vaccines containing CpG oligodeoxynucleotides

Abstract: We assessed the ability of several factors to increase the size of tumor-antigen-specific CD8 + T cell responses elicited by vaccines incorporating peptides and CpG-containing oligodeoxynucleotides (CpG). Neither granulocyte-macrophage colony-stimulating factor (GM-CSF) nor an immunogenic MHC class II-presented "helper" peptide increased the size of epitope-specific CD8 + T cell responses elicited by peptide+CpG-containing vaccines. In contrast, low-dose subcutaneous interleukin (IL)-2 dramatically increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 33 publications
2
18
0
1
Order By: Relevance
“…CpG also showed anti-tumour activity as such when immunized with TAAs ( Fig. 1C and D) as reported previously (Kochenderfer et al 2007;Davila et al 2003;Davila and Celis 2000;Miconnet et al 2002;Ballas et al 2001). Immunization with TAAs alone had no effects on the tumour growth and survival rate ( Fig.…”
Section: Effects Of Fsl-1 On Tumour Growth In Vivosupporting
confidence: 76%
See 1 more Smart Citation
“…CpG also showed anti-tumour activity as such when immunized with TAAs ( Fig. 1C and D) as reported previously (Kochenderfer et al 2007;Davila et al 2003;Davila and Celis 2000;Miconnet et al 2002;Ballas et al 2001). Immunization with TAAs alone had no effects on the tumour growth and survival rate ( Fig.…”
Section: Effects Of Fsl-1 On Tumour Growth In Vivosupporting
confidence: 76%
“…It has been demonstrated that the TLR9 ligand CpG induces Th1 response and reduces the growth rate of tumours through the induction of TAA-specific CTLs (Kochenderfer et al 2007;Davila et al 2003;Davila and Celis 2000;Miconnet et al 2002;Ballas et al 2001;Krieg 2006Krieg , 2007. However, it remains unknown how Th2 inducers such as the TLR2 ligand FSL-1 (Kiura et al 2006) affect the growth rate of tumour.…”
Section: Anti-tumour Activity Of Fsl-1mentioning
confidence: 95%
“…CpGs promote expansion of antigen-specific CD8 + T cells to high numbers (29,32,33), with features critical to immune protection such as high T cell receptor avidity (34), strong clonotypic bursts, and multifunctionality (D.E. Speiser, unpublished observation).…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive vaccination with peptides in IFA can generate large numbers of epitope-specific CD8 þ T cells (37), but peptides in IFA vaccines have only rarely caused objective antitumor responses (1). Vaccination of mice with the TRP-2 180-188 peptide in IFA was not effective at causing inhibition of B16 growth (21), and vaccination with TRP-2 180-188 in IFA elicited very small CD8 þ T-cell responses (38,39). The size of epitope-specific CD8 þ T-cell responses elicited by peptide in IFA vaccines was dramatically increased by the addition of oligodeoxynucleotides containing unmethylated CpG motifs (CpGs; Refs 9,[38][39][40].…”
Section: Peptide Vaccinesmentioning
confidence: 99%
“…Vaccination of mice with the TRP-2 180-188 peptide in IFA was not effective at causing inhibition of B16 growth (21), and vaccination with TRP-2 180-188 in IFA elicited very small CD8 þ T-cell responses (38,39). The size of epitope-specific CD8 þ T-cell responses elicited by peptide in IFA vaccines was dramatically increased by the addition of oligodeoxynucleotides containing unmethylated CpG motifs (CpGs; Refs 9,[38][39][40]. CpGs have been divided into three classes: class A CpGs, class B CpGs, and class C CpGs (41,42).…”
Section: Peptide Vaccinesmentioning
confidence: 99%